Long-Term Results after Treatment of Very Low-, Low-, and High-Risk Thyroid Cancers in a Combined Setting of Thyroidectomy and Radio Ablation Therapy in Euthyroidism - Nikos Emmanouilidis; Harald Schrem; Michael Winkler; Jürgen Klempnauer; Georg F. W. Scheumann (International Journal of Endocrinology, 2013)
Introduction. Differentiated thyroid cancer treatment usually consists of thyroidectomy and radio ablation in hypothyroidism 4-6 weeks after surgery. Replacing hypothyroidism by recombinant human thyroid stimulating hormone can facilitate radio ablation in euthyroidism within one week after surgery. The outcome of this approach was investigated. Methods. This is a prospective randomized trial to compare thyroidectomy and radio ablation within a few days after preconditioning with recombinant human thyroid stimulating hormone versus thyroidectomy and radio ablation separated by four weeks of L-T4 withdrawal. Tumors were graded into very low-, low- , or high-risk tumors. Recurrence-free survival was confirmed at follow-up controls by neck ultrasound and serum thyroglobulin. Suspected tumor recurrence was treated by additional radio ablation or surgery. Quality-of-life questionnaires with additional evaluation of job performance and sick-leave time were used in all patients. Results. Radio ablation in euthyroidism in quick succession after thyroidectomy did not lead to higher tumor recurrence rates of differentiated thyroid cancers in any risk category and was significantly advantageous with respect to quality-of-life (P<0.001), sick-leave time (P<0.001), and job performance (P=0.002). Conclusion. Recombinant human thyroid stimulating hormone can be used safely and with good efficacy to allow radio ablation under sustained euthyroidism within one week after thyroidectomy.